The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1292/jvms.66.1097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopamine, Dobutamine, Amrinone and Milrinone on Regional Blood Flow in Isoflurane Anesthetized Dogs

Abstract: ABSTRACT. The effects of cyclic AMP increasing cardiotonics (dopamine, dobutamine, amrinone and milrinone) on the blood flow in most organs were compared using colored microsphere technique in isoflurane-anesthetized dogs. Dopamine increased blood flow in ventricular myocardium. Furthermore dopamine induced the increase in blood flow in intestine and kidney at low to middle dose, but not at high dose. Dobutamine induced the highest increase in blood flow in ventricular myocardium and skeletal muscle among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
2
10
0
4
Order By: Relevance
“…This is relevant because higher doses of dopamine must be used to generate higher blood pressures and dose-dependent effects of dopamine on regional perfusion exist. Specifically, dopamine increases gastric blood flow in dogs at moderate doses but decreases blood flow to the stomach at higher doses [12].…”
Section: Norepinephrinementioning
confidence: 96%
“…This is relevant because higher doses of dopamine must be used to generate higher blood pressures and dose-dependent effects of dopamine on regional perfusion exist. Specifically, dopamine increases gastric blood flow in dogs at moderate doses but decreases blood flow to the stomach at higher doses [12].…”
Section: Norepinephrinementioning
confidence: 96%
“…[10] In their study on healthy dogs with different inotropic agents, Tobato et al found that the renal blood flow was altered with the use of amrinone and milrinone, though these alterations were not statistically significant. [11] However, all members of the type III PDE inhibitors have similar clinical effects, as the former three drugs, being biypridine derivatives, are chemically diverse from enoximone, an imidazole derivative. This chemical diversity can be speculated as the reason for different effects on the renal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…O mesmo efeito foi observado em cães, nos quais a dose de 1,2µg/kg/min aumentou em 38% o fluxo sanguíneo renal, sem alterar a pressão sanguínea arterial (McNay et al, 1965). Baixas doses de dopamina estimulam receptores D1 no leito vascular renal, induzindo a vasodilatação e aumento do fluxo sanguíneo renal (Tobata et al, 2004), mas doses altas, capazes de estimular receptores α-adrenérgicos, levam a vasoconstrição renal e de outros efeitos vasculares (Furukawa et al, 2002). Enquanto a estimulação de receptores D1 causa vasodilatação de forma direta, mediada pela via AMPc/PKA, a ação dos receptores tipo D2 é um pouco mais complexa.…”
Section: Introductionunclassified